FRI0312 The frequency and severity of patient-reported symptoms in giant cell arteritis. (15th June 2017) - Monti, S; Leong, A; Robson, J; Craven, A; Merkel, PA; Watts, R; Luqmani, R
Abstract : Background: A better understanding of the patients' perspectives is pivotal in the development of patient-reported outcomes (PROs) in vasculitis. Objectives: To assessed patients' perspective of disease amongst cases with Giant Cell Arteritis (GCA) compared to comparator illnesses mimicking large vessel vasculitis (LVV) included in the Diagnostic and Classification Criteria in Vasculitis Study (DCVAS) database. Methods: Patient Description of Illness (PDI) forms were circulated amongst Centres participating in the DCVAS study. The PDI form records up to 10 free-text severity ranked symptoms in descending order of severity, a body-map to localise the sites of pain and a free-text short summary of illness description. Free text was reorganized through content and thematic analysis. Results: PDI forms from 89 patients with GCA and 28 comparators (COM) were analysed. There was no difference in age and sex distribution between groups (mean age 70±8 for GCA and 69±12 for COM). The symptoms description and frequency of the first most severe aspect of disease, including the patient's own words, is presented in Table 1 . The symptom regarded as the most severe by both groups was headache. While there were no differences in the frequency of sudden visual loss, visual symptoms were reported more commonly as the most severe feature by COM vs GCA (21% vs 8%, p=0.05). Arthralgia was more frequently reported by COM vs GCA (11% vs 1%, p=0.01). Headache was the most frequently reported symptom in both groups. Patients with GCA reported jaw claudication (37%) as the second most frequently reported symptom, while COM reported arthralgia/arthritis (32%). Shoulder/neck pain was the third most important symptom in GCA (33%), while fatigue was the third most common complaint among COM (21%). Fatigue was reported as the fourth most common feature by 30% of GCA patients. Conclusions: Headache was the most frequent and most severe symptom reported by patients with GCA and comparators. However, the reported frequencies and severities of other symptoms were significantly different between the two groups. Disclosure of Interest: None declared